Leptospirose: epidemologia da enfermidade em humanos e estudo soroepidemiológico em equinos do Amazonas, Brasil - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2021)
Leptospirosis is a zoonotic disease that is potentially fatal to humans and has the capacity to generate health and economic losses to several animal species. If we consider the existence of favorable environmental conditions for the occurrence of leptospirosis, the potential amplitude of the disease is magnified, justifying the need for epidemiological studies in both human and animal populations. Thus, this thesis developed a retrospective epidemiological study of cases of leptospirosis infection in humans in the State of Amazonas (Chapter I), as well as a seroepidemiological study in horses in Manaus and the metropolitan region (Chapters II and III). The data for the development of Chapter I were obtained from the computer department of the Brazilian National Health System (DATASUS) using the data of diseases and aggravations of notification from SINAN (Sistema de Informações de Agravos de Notificação – Notifiable Diseases Information System), referring to cases of leptospirosis in the municipalities of the state of Amazonas in the period from 2010 to 2019. The information about the cases of infection in humans in these years was correlated to meteorological data from the BDMEP (Meteorological Database from INMET - National Institute of Meteorology), which are precipitation, temperature, and humidity from the conventional meteorological stations of the INMET station network in the state of Amazonas. The highest number of leptospirosis infections in humans occurred in the municipalities of Manaus (n=422), Boca do Acre (n=41), and Parintins (n=31). The municipality of Boca do Acre had the highest cumulative incidence of leptospirosis infection in humans during the study period (121.4 cases per 100,000 inhabitants). As a main result, it was found that the occurrence of the infection occurs more frequently in the home environment in the state of Amazonas; therefore, the home environment is an important determinant of transmission, and a likely consequence of the precarious environmental conditions existing in the home and peridomicile. Associated to this result and considering the climatic and environmental characteristics of the region and the information on the increasing number of horses living in urban areas of Manaus, the risk of exposure and contamination of humans and other susceptible animals has been increasing as the equine population has grown in recent years. Thus, for chapters II and III, a literature review on the disease in these animals was performed, and the frequency of leptospirosis in horses in Manaus and the Amazon metropolitan region was determined. Equine serum samples were collected and sent for serological diagnosis of leptospirosis to the Leptospirosis Diagnostic Laboratory at the Federal University of Santa Maria (UFSM). Serum samples were tested (n = 198) for the presence of anti-Leptospira antibodies by the microscopic microagglutination assay, as recommended by the World Health Organization. The results obtained in the study indicated a high frequency (n=92 / 46.46%) of seropositivity for Leptospira spp. in horses in the state of Amazonas, indicating the existence of a high frequency of reaction to the serogroups Icterohaemorrhagiae and Pyrogenes. With the increase in the equine herd in the region and, consequently, greater interaction between breeders and animals, the identification of reagent serogroups of Leptospira spp. signals the possible existence of reservoirs and pathogenic strains for other animals and humans. As a conclusion, in the sum of the three chapters, it can be inferred that the greatest risk of leptospirosis in the state of Amazonas is urban, highly related to environmental conditions favorable to the development and maintenance of the bacteria in the environment, especially when associated with low levels of basic sanitation. The seroprevalence obtained for horses shows that the disease affects these animals, potentially bringing economic and sanitary losses to farmers, considering the potential reservoir and transmission that horses can have. Lastly, epidemiological studies on leptospirosis should be permanent and periodic, so that up-to-date data on the disease can be maintained, which could, in this way, facilitate the implementation and adjustment of leptospirosis prevention and control measures in the state of Amazonas.
Keywords: Amazônia; Leptospira interrogans; Zoonose; Saúde Pública; Sanidade animal; Cavalos; CNPQ::Ciências Sociais Aplicadas